Application Of Starfruit Juice Therapy To Lower Blood Pressure In Hypertensive Patients Applied With Virginia Henderson's Theory - Devi Ratna Sari A; Mariza Arfianti (Journal of Multidisciplinary Research, 2026)
Hypertension is a disease that can affect anyone, regardless of age or gender. Hypertension is often referred to as the silent killer because it is a potentially fatal disease. While high blood pressure does not directly kill patients, it can lead to other fatal illnesses and increase the risk of heart attack, heart failure, stroke, and kidney failure (Zamai et al., 2016). The purpose of this study was to investigate the application of starfruit juice therapy to lower blood pressure in hypertensive patients using the Virginia Henderson Theory in the Jembatan Kecil Community Health Center (Puskesmas) in Bengkulu City. In this case study, the researchers used two clients who were assessed based on their complaints and provided nursing care tailored to their diagnoses (Notoatmodjo, 2012). The results of the nursing care provided for hypertension cases demonstrated an adaptive response in the patients. These results demonstrate that the Virginia Henderson Theory is effective for hypertensive patients. Therefore, the Virginia Henderson Theory can be considered a method for providing quality nursing care. The Virginia Henderson Theory can be applied effectively in hypertension-focused care. Suggestions for patients and families to increase their knowledge about the disease they are suffering from so that patients can always maintain their health, and it is hoped that the patient's family can provide starfruit juice to prevent hypertension.